Case report: Simultaneous occurrence of primary pulmonary lymphoma and opportunistic infections in a patient with chronic myeloid leukemia - Bi, Yazhen; Feng, Saran; Shang, Jinyu; Liu, Qian; Wang, Yan (Frontiers in Oncology, 2022)
Abstract Background: The occurrence of primary pulmonary lymphoma (PPL) as a secondary malignancy in patients diagnosed with chronic myeloid leukemia (CML) is extremely rare. As the clinical manifestations are atypical, most patients with PPL tend to be misdiagnosed with pneumonia. When the radiographic features of PPL and pulmonary infection overlap, clinicians can be confused about the diagnosis. Here, we report the first case of coexistence of PPL and opportunistic infections in a patient with CML in chronic phase (CML-CP). Case presentation: A 55-year-old woman presented with three weeks of hemorrhage of the oral mucosa at the Department of Hematology. After undergoing various examinations, she was diagnosed with CML-CP and was started on imatinib (400 mg/daily). Due to sudden respiratory distress, the patient was admitted to the respiratory intensive care unit 11 months later. Chest computed tomography (CT) revealed ground-glass opacities, patchy shadows, and multiple nodules in both lungs and enlarged mediastinal lymph nodes. The combination of biapenem and voriconazole antibiotic treatments was effective. The patient's respiratory distress was relieved, but there was intermittent coughing. In the following time, the patient developed a fever, and the imaging findings indicated progression of the disease in both lungs. Bronchoalveolar lavage (BAL) identified pathogens of multiple opportunistic infections. The coexistence of lymphomatoid granulomatosis (LYG) was not confirmed in this patient until a second CT-guided biopsy was performed. Ultimately, the patient underwent chemotherapy in time and is currently alive today. Conclusions: When the patient's recurrent respiratory symptoms and imaging findings do not coincide, secondary tumors should be considered in addition to infection as a diagnosis. In these cases, multiple pathological tissue biopsies should be performed.